Learning style preferences and accounting students achievement - Zainon, Saunah; Mohamed Sadique, Raziah Bi; Abdullah, Aryani (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2004)
This study explores the effects of learning styles adopted by students on their academic performance. The learning styles examined are kinesthetic, visual, and auditory. Students from semesters two and six were randomly selected as the sample. The Pearson correlation coefficient and the t-test were used to analyze the data. The analysis shows that there is no dominant learning style adopted by either group; however, the results indicated that 44.3% of semester two students preferred the visual learning style, while 35.2% of semester six students preferred the kinesthetic learning style. The study reveals that there is no significant relationship between the learning styles adopted by students and their performance. The findings suggest that learning styles might not be the sole factor affecting academic performance. Furthermore, the study indicates that many respondents are unaware of their specific learning style or which type they should adopt.